Personal identity in theological perspective - Lints, Richard; Horton, Michael Scott; Talbot, Mark R. (Eerdmans, 2006)
The turbulence and confusion of contemporary life should motivate us to ask the big questions of life anew and to reexamine the disastrous naturalism of the twentieth century. This volume gathers well-known thinkers from a breadth of confessional Christian traditions who share a passionate interest in better understanding the nature of persons. The contributors to Personal Identity in Theological Perspective aim to recover the ancient biblical account of human beings as made "in the image of God." Their essays fall naturally into three divisions - retrieving historical discussions of human identity, presenting contemporary challenges to a distinctively Christian anthropology, and offering constructive proposals toward a richer understanding of persons. This volume will provoke discussion and debate on the fundamental question What does it mean to be human? Contributors: Stanley J. Grenz Michael S. Horton Stanton L. Jones David H. Kelsey Richard Lints Nancey Murphy Mark R. Talbot William C. Weinrich Robert Louis Wilken Mark A. Yarhouse - The turbulence and confusion of contemporary life should motivate us to ask the big questions of life anew and to reexamine the disastrous naturalism of the twentieth century. This volume gathers well-known thinkers from a breadth of confessional Christian traditions who share a passionate interest in better understanding the nature of persons. The contributors to Personal Identity in Theological Perspective aim to recover the ancient biblical account of human beings as made "in the image of God." Their essays fall naturally into three divisions - retrieving historical discussions of human identity, presenting contemporary challenges to a distinctively Christian anthropology, and offering constructive proposals toward a richer understanding of persons. This volume will provoke discussion and debate on the fundamental question What does it mean to be human?